5(2+w)=4(7+w)

Simple and best practice solution for 5(2+w)=4(7+w) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2+w)=4(7+w) equation:



5(2+w)=4(7+w)
We move all terms to the left:
5(2+w)-(4(7+w))=0
We add all the numbers together, and all the variables
5(w+2)-(4(w+7))=0
We multiply parentheses
5w-(4(w+7))+10=0
We calculate terms in parentheses: -(4(w+7)), so:
4(w+7)
We multiply parentheses
4w+28
Back to the equation:
-(4w+28)
We get rid of parentheses
5w-4w-28+10=0
We add all the numbers together, and all the variables
w-18=0
We move all terms containing w to the left, all other terms to the right
w=18

See similar equations:

| x=x+3x+52 | | 5x+5x=189 | | 2m/3=4 | | 6-4v=-2 | | 14=4x+18 | | 3=y/3+4 | | 11/6y-14=-3 | | 8(u-2)=-32 | | 61=8v-3 | | 15c=-9c | | 3/5a+6=10 | | 20(13x+22)=-30(x-4) | | 6x-5=2x-0.8 | | (1/3x+11)^2=50 | | 5u-3/4+u-7/5=8 | | 3.56x+7.56x+9.12=50.58 | | 7(1.054x+1)=11 | | 4b(-5b-3)-2(b^2-7b-4)=0 | |  4+z-(3+2z)=-z-3(5-2)/7 | | x^2-35x-147=0 | | 33+8y=45 | | 3-5m=12 | | 11x-8+13x-4=180 | | a=9(a+10)= | | a=9(a=10) | | 3m(3m+6)-3(m^2+4m+1)=0 | | 7x^2-15x-32=0 | | x2+2x+19=0 | | x=(-5^)^2 | | x=(-5^2 | | 5x÷3-2=1÷3(5x-6) | | Y=6÷4x^2-6 |

Equations solver categories